A Profile of Repeat Offending by Children and Young People in England and Wales - Coleman, Isabel; Afonso, Les; Huber, Johannes (International Journal of Population Data Science, 2025)
Objectives This report aims to analyse the characteristics of prolific young offenders in England and Wales. It seeks to identify factors that contribute to reoffending by adolescents, explore demographic profiles, and the factors which set these individuals apart. Method This analysis utilizes newly linked administrative datasets to expand significantly on prior statistics such as (Characteristics of Prolific Offenders, 2000-2021) and (Assessing the needs of sentenced children in the Youth Justice System - GOV.UK). Analysts identified 18 year old offenders convicted in magistrates’ or crown court in 2019, and divided these into prolific (3 or more youth convictions) and nonprolific young offenders (less than 3 youth convictions). Records from the newly linked offender assessment system were then attached to explore a spectrum of over 200 assessment criteria to identify where needs diverged the most. Results This analysis is due for publication as official statistics on March 20th. Under Office of Statistics Regulation guidelines, and to comply with the Statistics and Registration Service Act 2007, it is not possible to share results before publication. The report will include data on demographics, youth and adult offending behaviour, sentencing, as well as criminogenic and responsivity needs. The accompanying technical guide serves both to support the statistics publication, and researchers seeking to use these datasets in their own research. Conclusion The use of linked administrative datasets is changing the insights which official statistics can provide. The findings presented in this paper will be used by policy teams across the justice system to inform sentencing policy and interventions.